Velocities, imaging and waveform inversion : the evolution of characterising the Earth's subsurface - Jones, Ian F. 1956- (EAGE Publications, 2018)
This book subsurface is part of the author EAGE Education Tour and will be a fusion of practical industrial elements, concentrating on the origin and nature of the geological complexities that give rise to imaging problems, as well as a physical (rather than mathematical) understanding of subsurface parameter estimation, and will also look at some possible future directions. The course is designed for: practising geoscientists who desire to better understand the principles and limitations of both current and emerging technologies involved in subsurface parameter estimation and imaging and geoscience students. Following this course, participants should ideally understand how contemporary velocity estimation methods work, and what approximations are involved in obtaining computationally tractable solutions. In using sound waves to characterise the Earth's subsurface, we can employ ray theory and/or wave theory, and both migration algorithms and parameter estimation schemes employ one or other of these theoretical descriptions.